2013
DOI: 10.1371/journal.ppat.1003225
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Structure of Victorivirus HvV190S Suggests Coat Proteins in Most Totiviruses Share a Conserved Core

Abstract: Double-stranded (ds)RNA fungal viruses are currently assigned to six different families. Those from the family Totiviridae are characterized by nonsegmented genomes and single-layer capsids, 300–450 Å in diameter. Helminthosporium victoriae virus 190S (HvV190S), prototype of recently recognized genus Victorivirus, infects the filamentous fungus Helminthosporium victoriae (telomorph: Cochliobolus victoriae), which is the causal agent of Victoria blight of oats. The HvV190S genome is 5179 bp long and encompasses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 67 publications
(117 reference statements)
4
43
1
Order By: Relevance
“…As expected for totiviruses (32,(35)(36)(37)(38)(39), a surface view of the 3D reconstruction revealed that GLV appears to possess a so-called "Tϭ2" capsid (34) comprising 120 CP subunits in a Tϭ1 lattice ( Fig. 4A and C).…”
Section: Initial Characterizations Of Virions Used For Cryo-tem Studiessupporting
confidence: 62%
See 3 more Smart Citations
“…As expected for totiviruses (32,(35)(36)(37)(38)(39), a surface view of the 3D reconstruction revealed that GLV appears to possess a so-called "Tϭ2" capsid (34) comprising 120 CP subunits in a Tϭ1 lattice ( Fig. 4A and C).…”
Section: Initial Characterizations Of Virions Used For Cryo-tem Studiessupporting
confidence: 62%
“…The Segger v1.7 tool in the Chimera visualization package (48) was used to segment out individual CP-A and CP-B subunits in the final map and to examine interactions between them as described previously (38). Briefly, segmentation is obtained with this tool by means of an iterative procedure, starting from an initial arbitrary assignment of density regions to the two subunits and then refining those assignments in a semiautomatic manner by imposing additional restrictions.…”
Section: Protozoan Cultures and Virion Purificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was described that the core region in the crystal structure of ScV-L-A CP composed by helix 3-5 (aa 85-139) and helix 12-13 (aa 345-383) correspond closely in size and location to helices 2-3 (aa 84-122) and H10-12 (aa 350-397) of Helminthosporium victoriae virus 190S (HvV190S) CP, both members of different genera totiviruses. This centrally located stretch of residues with predominantly helical content was observed too in predicted secondary structures of CPs of representative members of Victorivirus, Giardiavirus, Leishmaniavirus, and Trichomonasvirus genera, suggesting a conservation of this helical core in Totiviridae family [28]. We compared the predicted secondary structure of CP of several totiviruses (Fig.…”
Section: Discussionmentioning
confidence: 90%